The Factors of involved with the accute respiratory infection to the fabrication worker PT.X: No - Sukriyadi (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Accute Respiratory Infection (ARI) is one of the disease causes of work which the effect to worker and attack to the top respiratory system, it is due to of environment factor exposure in work place. This observation is use of cross sectional desain to sample of worker. Data collection is do the 57 fabrication worker.The data is analyzed by bivariat analyze. The result of observation are a half of the worker has ARI occurred. The factors of involved to ARI are smoking (P value =0,025), working periode (P value = 0,017), age of worker (p value = 0,017), Using PPE of mask (p value = 0,018), dust exposure (p=0,004). Therefore, for worker must to do use PPE of mask when working, than give socialization of smoking danger to the worker that is is cause of ARI to the worker.